A modified approach to in-school victimization, authoritative school climate, and student feelings of safety. Issue 4 (8th August 2021) - Abad, Daniel; Almanza, Matthew G.; Melde, Chris; Cobbina, Jennifer; Heinze, Justin
ABSTRACT: Decades of research on fear of victimization suggest individuals draw upon their perceived risk of victimization in their development of fear, in what has become known as the risk assessment framework. Drawing on recent research on the influence of school climate on student reports of fear and safety, the current study seeks to determine whether school climate influences student risk perceptions and fear, consistent with the risk assessment framework. Utilizing a sample of elementary and high school students in Flint, Michigan, findings reveal that school climate is not correlated with student fear after accounting for factors such as prior student victimization, school disorder, and the perceived risk of victimization. Implications for these findings are discussed.